Factors Affecting The Frequency and Amount of Purchase Value in Online Food Delivery Apps - Shidqi, Salman Fauzan; Sumarwan, Ujang; Nurhayati, Popong (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Currently, the trend of using online food delivery applications in Indonesia is growing. Many people are buying food or simply searching for information about available restaurants through food delivery apps. Indonesia itself has become one of the countries with the highest number of internet users utilizing online food delivery applications in the world.Purpose: This research aims to determine the factors that influence repeat purchase decisions on online food delivery applications, which are based on purchase frequency and total purchase value. Design/methodology/approach: The analysis techniques used are descriptive analysis and logistic regression analysis. Findings/Result: The research results showed that product intrinsic factors and loyalty had a significant effect on purchase frequency, while product extrinsic factors, motivation factors, and situational factors did not have a significant effect on purchase frequency. Situational factors and loyalty have a significant effect on the total purchase value, while product intrinsic factors, product extrinsic factors, and motivation factors do not significantly influence the total purchase value.Conclusion: This research shows that a person's purchase frequency is influenced by the intrinsic qualities of the product being sold and by loyalty, where the individual is accustomed to buying the product. Additionally, the total purchase value on food delivery apps is influenced by situational factors and loyalty, where situational factors, such as ongoing promotions, also have a significant impact.Originality/value (State of the art): This research attempts to explain which factors can influence a person in purchasing a product based on the purchase frequency and the total purchase value. Keywords: loyalty factors, product intrinsic factors, purchase frequency, situation factors, total purchase value